Development of Modified Circuit Training in Basketball Learning to Improve Basic Technical Skills and Student Learning Motivation at SMKN 1 Sikur - Qitfirul Mauludi; Didik Daniyantara; Gani Prasetyo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Basketball is one of the popular sports taught in physical education because it develops students’ motor skills, coordination, cooperation, discipline, and motivation to participate in learning. However, the implementation of basketball instruction at SMKN 1 Sikur is still constrained by students’ low mastery of basic techniques and limited learning motivation. These conditions are related to limited facilities, a large number of students in each class, and the continued use of conventional teaching methods. A circuit-based approach may provide varied and active practice stations that accommodate large classes and optimize the use of available facilities. This study aimed to develop a modified circuit training-based basketball learning model and determine its feasibility and effectiveness in improving students’ basic basketball skills and learning motivation. This research used a research and development method based on the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The participants were 36 tenth-grade students of the Visual Communication Design program at SMKN 1 Sikur. Data were collected using material-expert and field-practitioner validation sheets, the AAHPERD Basketball Skill Test covering dribbling, passing, and shooting, and a Likert-scale questionnaire measuring learning motivation. The data were analyzed using a paired-samples t-test with a significance level of α = 0.05. The results showed that the developed model was categorized as “Very Feasible,” receiving scores of 88.5% from material experts and 91.2% from field practitioners. Students’ average basic basketball skill score increased from 54.30 in the pretest to 78.65 in the posttest, with a statistically significant difference (p < 0.05). Learning motivation also increased from 58% (“Sufficient”) to 85% (“Very High”). Therefore, the modified circuit training-based basketball learning model is feasible and effective for improving basic basketball skills and learning motivation in vocational high school physical education.